2018
DOI: 10.1007/s00246-018-1841-8
|View full text |Cite
|
Sign up to set email alerts
|

Study on ECG in the Adolescent

Abstract: Normal ECG values in newborns, infants, and children have been collected and published. ECG in the adolescent, however, remains, to be collected and studied. The present study was designed and carried out to establish the normal ECG standards in male and female adolescents. A total of 898 school children and adolescents screened and examined as healthy were divided by age and sex into 6-9, 9-13, and 13-18 years age-groups. A 12 lead conventional ECG was recorded in 10 mm/mV and 25 mm/s, utilizing an automated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
5
13
2
Order By: Relevance
“…Lue et 1327 al. [22] detected right branch block prevalence as 0.32% in their study with 432166 cases in the age range of 6-20. Pelliccia et al [30] found right branch block prevalence as 1% in their study with 32652 adolescents and young people.…”
Section: Adolescence and Gendermentioning
confidence: 83%
See 1 more Smart Citation
“…Lue et 1327 al. [22] detected right branch block prevalence as 0.32% in their study with 432166 cases in the age range of 6-20. Pelliccia et al [30] found right branch block prevalence as 1% in their study with 32652 adolescents and young people.…”
Section: Adolescence and Gendermentioning
confidence: 83%
“…Mean P axis was found 49°in our study. Mean P axis was detected as 42°by Rijnbeek et al [10] 42°by Lue et al [22], 47°by Semizel et al [2] and 47°by Uygur et al…”
Section: P Axismentioning
confidence: 97%
“…After conducting a thorough review of the literature, we identified five studies to judge on whether our reference values were consistent with those already published or conversely they raised new questions. However, although very relevant, two were not retained in our analysis as the age groups considered were different from ours (6-9, 9-13 and 13-18 years for the first and 0-9 to 90-99 years for the second) 4,15 16 . For these two studies, median values and 2 and 98 percentile values are available.…”
Section: Ecg Parameters Comparisonmentioning
confidence: 88%
“…As part of comprehensive cardiac assessment, an electrocardiogram (ECG) and a cardiac ultrasound were obtained on the subjects. Currently, no harmonized reference values for ECG and echocardiographic parameters in children are available 4,5 . Having these reference values thus appears crucial to ensure the relevant medical care of young patients 6,7 .…”
mentioning
confidence: 99%
“…Therefore, in our study, the electrodes were placed under the breast tissue but the amplitudes were still higher in boys in the Q, R and S wave-amplitudes. Also, Lue et al (28) stated that ECG sex difference began to appear at the earliest at ages 6–9 years, and it occurred mostly at ages 9–13 years and 13–18 years, reflecting the anatomic and physiologic consequences of puberty (28). Therefore, other factors may contribute to this difference besides breast tissue.…”
Section: Discussionmentioning
confidence: 99%